Views On Teaching Alisher Navoy's Creativity - Marjona Toshpulatova (Euro Asian Journal Publishing, 2024)
The article expresses Alisher Navoi's views on teaching the epic "Khamsa". Also, the study of the problems and prospects of teaching the thinker's creativity at school from the perspective of scientists is interpreted. The scientific-theoretical foundations of learning Lero-epic works at the educational stages are described.
Keywords: Alisher Navoi; Khamsa; pedagogical views